SiCN: SiCN Nanofibers with a Diameter Below 100 nm Synthesized via Concerted Block Copolymer Formation, Microphase Separation, and Crosslinking (Small 7/2013). Issue 7 (2nd April 2013) - Pillai, Saravana K. T.; Kretschmer, Winfried P.; Denner, Christine; Motz, Günter; Hund, Markus; Fery, Andreas; Trebbin, Martin; Förster, Stefan; Kempe, Rhett
<x xml:space="preserve">Abstract</x> SiCN fibers with a mean diameter of 50 nm and an aspect ratio of up to 100 are produced in a two‐step process by R. Kempe and co‐workers. The key step to fabricate the longitudinal and crosssectional views of the mesofibers shown here is a concerted block‐copolymer synthesis, microphase separation, and cross linking at 140 °C followed by pyrolysis at 1100 °C. Inexpensive components like a commercially available silazane and polyethylene are linked. The fibers may find application in electronic devices, as components of ceramic matrix composites, as fiber beds in hightemperature nano‐filtering like diesel fine dust removal, or as thermally robust and chemically inert catalyst supports. Furthermore, the SiCN nanofibers introduced on page 984 are a promising alternative to ultrathin carbon fibers, due to their oxidation resistance. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>